Cover Picture: In Situ Formation of Co9S8/N‐C Hollow Nanospheres by Pyrolysis and Sulfurization of ZIF‐67 for High‐Performance Lithium‐Ion Batteries (Chem. Eur. J. 40/2017). Issue 40 (30th May 2017) - Zeng, Peiyuan; Li, Jianwen; Ye, Ming; Zhuo, Kaifeng; Fang, Zhen
Abstract : A nanocomposite based on the homogeneous dispersion of Co9 S8 nanoparticles within the shell of N‐rich carbon hollow spheres (Co9 S8 /N‐C) was prepared by an in situ pyrolysis and sulfurization process, employing the Co II ‐imidazole coordination polymer ZIF‐67 as the precursor. The as‐prepared Co9 S8 /N‐C hollow nanospheres exhibit good electrochemical performance and long‐term cycling stability (≈784 mAh g −1 at 1 C after 400 cycles) when applied as anode material for lithium‐ion batteries, which likely results from the unique hollow hybrid structures. More information can be found in the Full Paper by Z. Fang et al. on page 9517 .